Peran Sastra dalam Menyebarkan Nilai-Nilai Keislaman pada Masa Dinasti Abbasiyah - Amanda Maharani Sandrina; Tenny Sudjatnika (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This research discusses the role of literature during the Abbasid Dynasty as a means of spreading Islamic values in the middle of the development of Islamic culture and science. At this time, literature not only functioned as a form of artistic expression, but also as a medium of moral learning, preaching, and social criticism that could easily be accepted by the wider community. The purpose of this study is to analyze how Islamic values were inserted in the literary works of the Abbasid era and to understand the social roles played by the great writers of the time. The study uses a qualitative approach with descriptive-historical method and literature study technique. Data sources come from various literary works in the form of poetry, prose, maqamah, and related secondary references. The content and context of the works of influential literary figures were analyzed. The results of the study show that literary works not only serve as a reflection of cultural development, but also an effective means of preaching using beautiful language selection, subtle moral messages, and strong emotional appeal. In conclusion, literature plays a major role in building awareness of Islamic values in people's lives and is one of the important foundations in strengthening Islamic civilization.